Performance dependent model for normal and high strength concretes - Folino, Paula (2012)
A new constitutive formulation, the so-called Performance Dependent Model valid for normal and high strength concretes is presented. The distinctive aspect of the proposed model is the consideration of relevant properties of concrete mix components in the evaluation of the involved material performance or quality at the macroscopic stand point. In this way, the composite features of concrete are appropriately taken into account. The model maximum strength surface is defined by means of the Performance Dependent Failure Criterion proposed by the authors in previous works. Concrete behaviors in pre and post peak regimes are modeled with a non uniform hardening law and an isotropic softening rule, respectively. To realistically reproduce the concrete ductility in pre and post peak regimes under different load scenarios, the hardening and softening laws are dened in terms of the acting conning pressure. Concrete dilatancy behavior is approached by means of a volumetric non associative fow rule. The softening law is embedded in fracture energy concepts for mode I and II types of failure. The model considers two main input material parameters: the uniaxial compressive strength and the performance parameter, a quality index defined in the context of the Performance Dependent Failure Criterion. The proposed constitutive model is able to capture the substantial differences in the failure behavior of normal and high strength concretes as well as of concretes with the same compressive strength but different mix components. The predictive capabilities of the model are demonstrated in the numerical analyses included in this paper where the numerical predictions are compared with experimental results related to concrete specimens of different qualities and subjected to stress histories under both compressive and tensile regimes.